Guilt, shame, and embarrassment: similar or different emotions? A comparison between Italians and Americans - Giorgetta, Cinzia; Strappini, Francesca; Capuozzo, Alessandra; Evangelista, Elisa; Magno, Antonella; Castelfranchi, Cristiano; Mancini, Francesco (Frontiers in Psychology, 2023)
Guilt, shame, and embarrassment represent affective experiences with social implications and diverse self-relevant negative affect. While the distinction between these emotion terms has been extensively investigated, little is known about how the they diverge and are related to each other and their cross-cultural differences. Here, we used a community sample (N=163) comprised of Americans and Italians and a scenario-based measure in which we asked participants to report the intensity of emotions that the story's main character would feel. The elements used to build the scenarios were based on a recent theoretical approach that proposes distinguishing cognitive, somatic, interoceptive, and behavioral ingredients to differentiate between these emotions. We hypothesized that these ingredients might effectively elicit the target emotions and that the main differences across these cultures would be associated with the emotion terms of shame/vergogna. Our findings suggest that these defining elements are effective in evoking experiences of guilt, shame, and embarrassment. Moreover, we found that shame was equally elicited by the Shame and Guilt Scenarios only in the American sample, thus suggesting a proximity between shame and guilt in the American sample compared to the Italian's terms of vergogna and colpa. These results suggest important implications for the psychology of moral emotions and highlight the importance of taking into account some cognitive factors, such as the quality of selfevaluation, the discrepancy between the actual self and the ideal self vs. the sense of perceived responsibility, and the different domains related to self-esteem.